Knowledge and attitude toward oral health behavior of overseas students during the COVID-19 pandemic. - Susanti, Isi; Pisarnturakit, Pagaporn Pantuwadee; Sanchavanakit, Neeracha (BMC Oral Health, 2023)
Background: The COVID-19 pandemic has impacted overseas students, including their oral health. Due to movement restrictions, limited living allowances, dental treatment costs, and health insurance fees, overseas students might be more concerned about their oral health. The objective of the present study was to determine the association of knowledge and attitude toward oral healthcare behavior of overseas university students staying in Thailand between January 2020 to July 2022 and explore the experiences of their oral health problems. Methods: A cross-sectional study was conducted using an online survey in English operated through the Google platform by convenience sampling among overseas Chulalongkorn University students. A newly developed self-administered questionnaire on knowledge and attitude toward oral health-related behavior and experiences in oral health problems was completed voluntarily. Descriptive statistics, Chi-square test, t-test, ANOVA, and Pearson correlations were employed using IBM SPSS version 29. Results: Of 311 overseas students, 55.6% were male. The average age of students was 27.5 ± 4.5 years. 68.81% of students were from ASEAN countries, and 73.31% studied in non-health science programs. The study fields, health and non-health sciences, were associated with knowledge score (p < 0.001) and attitude score (p = 0.004), whereas the type of health insurance had an association with behavior score (p = 0.014) and the student's perspective about dental visits (p = 0.014). Three hundred fifty-nine cases of oral health problems were experienced by 47.3% of overseas students. These problems consisted primarily of tooth hypersensitivity (21.2%), gingivitis (15.3%), caries (14%), cracked or broken tooth (10%), severe toothache (9%), fallen out filling (8%), and wisdom tooth pain (7.8%). There was an association between oral healthcare behavior and oral health problems (p < 0.001), and a negative correlation was found between behavior score and the number of oral health problems (p < 0.001, r=-0.204). Conclusion: The oral healthcare habits of overseas university students correlated positively with knowledge and attitude. A negative correlation was observed between behavior and the number of oral health problems. Furthermore, studying in health science programs impacted students' knowledge and attitude toward oral health, while dental treatment coverage insurance affected decisions for dental visits.